Analysis of Data Management in Sigi District Statistics Center - Anjung Budi Cahyono; Rajindra Rajindra; Haris Abd. Kadir (Universitas Muhammadiyah Palu, 2021)
This study aims to determine data management on the gross regional domestic product at the Central Bureau of Statistics of Sigi Regency. Management of Sigi Regency Gross Regional Domestic Product data shows several uses of the final product manifested in the form of